Modernising civil liability law in Europe, China, Brazil and Russia : texts and commentaries / Gert Brüggemeier ; foreword by Walter Van Gerven. - Brüggemeier, Gert, 1944- (Cambridge University Press, 2011)
Non-contractual liability, stemming from damage accountably caused to another, has been the subject of the PETL and DCFR VI European reform initiatives. Gert Brüggemeier, however, proposes alternative reforms which, instead of trying to overcome the differences between civil law (delict) and common law (torts), are restricted to civil liability. The focus is on the grounds of accountability, and stricter forms of liability are at the fore. Quasi-strict enterprise liability is introduced to fill the lacuna between personal fault and forms of strict liability. A commentary is included on recent legislation on civil liability in China, Brazil and Russia to demonstrate how these large countries try to come to grips with the challenges of 'risk society'.